2020
DOI: 10.1155/2020/7807856
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Physical Activity in MCI and Dementia

Abstract: Physical activity improves overall health and reduces the risk of many negative health outcomes and may be effective in improving cognition, independent functioning, and psychological health in older adults. Given the evidence linking physical activity with improvements in various aspects of health and functioning, interventions exploring pathways for decreasing risk of dementia in those with mild cognitive impairment (MCI) and improving outcomes for those with dementia are of critical importance. The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
116
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(132 citation statements)
references
References 91 publications
1
116
1
1
Order By: Relevance
“…22 Moreover, it is reported that physical activity/exercise may increase neurogenesis and synaptic plasticity. 11,23 Physical activity, especially aerobic exercise, is associated with increases in brainderived neurotrophic factor (BDNF), a factor that can stimulate neuronal cell growth and maintain neurons in good status. 24 Third, using neuroimaging techniques, additional evidence for the impact of physical activity on brain function and structure is reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Moreover, it is reported that physical activity/exercise may increase neurogenesis and synaptic plasticity. 11,23 Physical activity, especially aerobic exercise, is associated with increases in brainderived neurotrophic factor (BDNF), a factor that can stimulate neuronal cell growth and maintain neurons in good status. 24 Third, using neuroimaging techniques, additional evidence for the impact of physical activity on brain function and structure is reported.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported that physical activity/exercise can prevent the transition from MCI to dementia and that these interventions can improve some cognitive and noncognitive outcomes in this specific population at higher risk for dementia. 11 Given the above, the aim of this umbrella review, promoted by the European Geriatric Medicine Society, is to understand the effect of physical activity/exercise on improving cognitive and noncognitive outcomes in people with MCI/dementia.…”
mentioning
confidence: 99%
“…La actividad física también mejora la cognición, especialmente la memoria en deterioro cognitivo leve y la salud psicológica en la demencia (Nuzum et al, 2020). También evidencias actuales determinan que la actividad física está asociada con una disminución del riesgo de cáncer de próstata (Capece et al, 2020).…”
Section: Discussionunclassified
“…58,59 Even in the case of dementia, exercise science has established a body of both human and animal research demonstrating a strong role for aerobic activity. [60][61][62][63][64][65] The relationship between exercise in cognitive loss prevention remains less clear, but it is reasonable to presume that exercise promotion is at the very least prudent in mild cognitive impairment (MCI) and dementia. 65,66 In recent years, aquatic exercise has been promoted as a useful exercise option in both MCI and dementia.…”
Section: Aquatic Therapy Use In Dementiamentioning
confidence: 99%
“…The role of exercise in the preservation and improvement of cognitive function is becoming well‐established science however 58,59 . Even in the case of dementia, exercise science has established a body of both human and animal research demonstrating a strong role for aerobic activity 60‐65 . The relationship between exercise in cognitive loss prevention remains less clear, but it is reasonable to presume that exercise promotion is at the very least prudent in mild cognitive impairment (MCI) and dementia 65,66 .…”
Section: Aquatic Therapy Use In Dementiamentioning
confidence: 99%